Prompt neutrons from fission of 252Cf and 235U - Pringle, John Stephen (Department of Physics, 2016)
Measurements have been made of the n-n angular correlation for neutrons emitted in spontaneous fission of ²⁵²Cf and thermal-neutron- induced fission of ²³⁵U. The dependence of the angular correlation on the neutron detection threshold energy was investigated. These measurements and other experimental data on the fission spectrum and the neutron angular distribution are compared with Monte Carlo calculations based on the evaporation model. It is apparent that a model assuming isotropic evaporation of all neutrons from the moving fragments cannot adequately explain the observed distributions. No evidence was found favouring the emission of a fraction of the neutrons isotropically at scission, or during the fragment acceleration period.